PENGEMBANGAN BUDAYA UNGGUL UNTUK PEMBENTUKAN MUTU AKADEMIK PESERTA DIDIK DI MTsN 2 KOTA KEDIRI - ASAFILA, INA MACHLA; LESSY, ZULKIPLI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research examines the development of a culture of excellence in shaping academic quality at MTsN 2 Kediri City. So the aim of this research is to find out the development of a superior culture starting from the form of existing culture, how to develop it and the implications of developing a superior culture in shaping the academic quality of students. Researchers carry out research by going directly to the field to collect data and carry out data analysis in each process of conducting research. This research method is qualitative-descriptive. Data collection techniques use observation, interviews and documentation. Data analysis includes data reduction, data presentation and drawing conclusions. The research stages are the preparation, implementation and completion stages. The findings show that MTsN 2 Kediri City has a culture that is used as an advantage of the madrasa. Some of the cultures that exist at MTsN 2 Kediri City are a culture of achievement, a culture of literacy, a culture of research and supported by a spiritual culture and a culture of discipline with the aim of strengthening positive values ??in supporting the quality of students to shape the academic quality of the madrasah as well as providing facilities. The way madrasas develop a culture of excellence is by developing activities and programs from existing types of superior culture centered on the vision, mission and goals of the madrasa. The implications of developing a culture of excellence in shaping the academic quality of students are that developing a culture of excellence creates academic excellence, achievement excellence and improves students' discipline. ABSTRAKPenelitian ini mengkaji mengenai pengembangan budaya unggul dalam membentuk mutu akademik di MTsN 2 Kota Kediri. Sehingga tujuan dari penelitian ini yaitu untuk mengetahui pengembangan budaya unggul mulai dari wujud budaya yang ada, cara mengembangkannya serta implikasi pengembangan budaya unggul dalam membentuk mutu akademik peserta didik. Peneliti melaksanakan penelitian dengan turun langsung ke lapangan untuk menghimpun data dan melaksankan analisis data pada setiap proses pelaksanaan penelitian. Metode penelitian ini yaitu kualitatif-deskriptif. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Analisis data meliputi reduksi data, penyajian data dan penarikan kesimpulan. Tahapan penelitian yakni tahap persiapan, pelaksanaan dan penyelesaian. Dari hasil temuan menunjukkan bahwa MTsN 2 Kota Kediri memiliki budaya yang dijadikan sebagai keunggulan dari madrasah tersebut. Beberapa budaya yang ada di MTsN 2 Kota Kediri yaitu budaya budaya prestasi, budaya literasi, budaya riset dan didukung dengan budaya spiritual serta budaya disiplin dengan tujuan memperkuat nilai-nilai positif dalam menunjang kualitas peserta didiknya untuk membentuk mutu akademik madrasah juga memberikan fasilitas. Cara madrasah dalam mengembangkan budaya unggul yaitu dengan mengembangkan kegiatan dan program dari jenis budaya unggul yang ada dengan berpusat pada visi, misi dan tujuan madrasah. Implikasi pengembangan budaya unggul dalam membentuk mutu akademik peserta didik yaitu pengembangan budaya unggul menciptakan unggulan akademik, keunggulan prestasi dan menunggkatkan kedisiplinan peserta didik.